The Comfort of Strangers - Jinmi Adisa (IFRA-Nigeria, 1995)
The Comfort of Strangers gives detailed information on the background to the Rwandan refugee problem and a vivid portrayal of the effects of the mass exodus of Rwandans into Tanzania, Uganda, Burundi and Zaire. The global community has, over the past eighty years, put in place an international refugee regime to regularize the status and provide for the control of stateless people ail over the world. Although host communities may initially open their doors to large numbers of people fleeing fr...